2007
DOI: 10.1186/1471-230x-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in patients with gastrointestinal cancer: does knowledge of cancer diagnosis matter?

Abstract: Background: Gastrointestinal cancer is the first leading cause of cancer related deaths in men and the second among women in Iran. An investigation was carried out to examine anxiety and depression in this group of patients and to investigate whether the knowledge of cancer diagnosis affect their psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
117
5
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 34 publications
14
117
5
6
Order By: Relevance
“…These findings suggest that patients with lower educational level may have more difficulty in acquiring knowledge, understanding given information, and coping with problems. Contrary to our study, different studies have reported that educational level has no effect on anxiety and depression levels (Ozkan et al, 2007;Tavoli et al, 2007).…”
Section: Hads Scorescontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that patients with lower educational level may have more difficulty in acquiring knowledge, understanding given information, and coping with problems. Contrary to our study, different studies have reported that educational level has no effect on anxiety and depression levels (Ozkan et al, 2007;Tavoli et al, 2007).…”
Section: Hads Scorescontrasting
confidence: 99%
“…Contrary to our findings, a study has shown that middle-aged and old patients with GI cancer have higher anxiety levels (Ozkan et al, 2007). However, similar to our study, another study has shown that age has no effect on depression levels (Tavoli et al, 2007). On the other hand, different studies have reported that elder patients have higher anxiety and depression levels (Nikbakhsh et al, 2014).…”
Section: Hads Scoressupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, Tavoli et al (2007) performed a cross sectional study of anxiety and depression in 142 patients with gastrointestinal cancer, and found that psychiatric disorders occurred to lesser extent in patients who did not know their cancer diagnosis. Similarly in another study, it has been demonstrated that patients who are not aware of their cancer diagnosis had a more hopeful outlook to the outcome of treatment (Atesci et al, 2004).…”
Section: 309 Factors Associated With Psychological Characteristics Imentioning
confidence: 99%
“…From the literature, previous studies have evaluated the psychological status throughout all phases of cancer and highlight several symptoms, such as anxiety and depression, in patients with cancer (Pirl et al, 2004;Tavoli et al, 2007;Nelson et al, 2009;Jadoon et al, 2010;Dempster et al, 2011;Hulbert-Williams et al, 2011). In past decades, a growing number of studies, looking at cancer patients undergoing interventional procedure, suggest severe psychological distress occurs in patients with cancer (Wang et al, 2008) and some symptoms can inhibit healing and interfere with clinical outcomes (Martin et al, 2005;Schupp et al, 2005;Sims et al, 2006).…”
Section: Introductionmentioning
confidence: 99%